Endocytosis of AtRGS1 Is Regulated by the Autophagy Pathway after D-Glucose Stimulation - Yan, Quanquan; Wang, Jingchun; Fu, Zheng Qing; Chen, Wenli (Frontiers in Plant Science, 2017)
Sugar, as a signal molecule, has significant functions in signal transduction in which the seven-transmembrane regulator of G-protein signaling (RGS1) protein participates. D-glucose causes endocytosis of the AtRGS1, leading to the physical uncoupling of AtRGS1 from AtGPA1 and thus a release of the GAP activity and concomitant sustained activation of G-protein signaling. Autophagy involves in massive degradation and recycling of cytoplasmic components to survive environmental stresses. The function of autophagy in AtRGS1 endocytosis during D-glucose stimulation has not been elucidated. In this study, we investigate the relationship between autophagy and AtRGS1 in response to D-glucose. Our findings demonstrated that AtRGS1 mediated the activation of autophagy by affecting the activities of the five functional groups of protein complexes and promoted the formation of autophagosomes under D-glucose application. When the autophagy pathway was interrupted, AtRGS1 recovery increased and endocytosis of ATRGS1 was inhibited, indicating that autophagy pathway plays an important role in regulating the endocytosis and recovery of AtRGS1 after D-glucose stimulation.